Evidence for a complex evolutionary history of mound building in the Australian nasute termites (Nasutitermitinae). (18th December 2018) - Beasley-Hall, Perry G; Chui, Juanita; Arab, Daej A; Lo, Nathan
Abstract: Termite mounds have intrigued humans for millennia. Despite great interest in their beautiful and often complex structures, the question of why termites acquired mound-building behaviour has received little attention. Here, we focus on two Australian lineages of the Nasutitermitinae (composed primarily of Nasutitermes and Tumulitermes spp.), which have evolved mound-building behaviour in parallel from arboreal and soil/wood-nesting ancestors, respectively. We used environmental niche modelling and ancestral niche reconstructions to investigate whether abiotic factors, including precipitation, temperature and soil composition, were associated with the repeated acquisition of mound building. Although we found strong evidence for ecological speciation leading to niche divergence in the nasutes, ultimately no abiotic variable was consistently correlated with mound-building behaviour. We also observed no trend in the variables limiting the environmental tolerances of mound builders. This suggests a more complex evolutionary history of mound building that cannot be explained by the abiotic factors we examined. Instead, biotic factors not considered here, e.g. colony expansion and protection, might have played a key role in the acquisition of this trait.